Performing social advocacy: A critical sociolinguistic analysis of selected songs of Beautiful Nubia - Saheed Omotayo Okesola (Journal of linguistics, culture and communication, 2024)
This study explores social advocacies in the songs of Segun Akinlolu (aka Beautiful Nubia). The data for the study comprises ten purposively selected songs by the artist. These songs are Seven Lifes, Owuro Lojo (How do you do?), Ma Ba Won So, Baba Mimo, Jangbalajugbu, Ohun Oju Nri, Table Turns, E K'omo L'ede, Small People’s Anthem, and Mind of Your Own. The study blends critical sociolinguistics and discourse historical approach (DHA) of critical discourse studies in data analysis. The analysis shows that through symbolism, imagery, juxtaposition, rhetorical question and irony, Beautiful Nubia prioritizes social advocacies in his songs by enlightening and raising people’s consciousness about patriotism, justice and equity, national courage and resilience, cultural preservation, and linguistic identity. The study concludes that Beautiful Nubia sees music and its performance as public enlightenment undertakings for sociopolitical advancement and societal repositioning.